2001
DOI: 10.1029/2000je001324
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of water ice in the outer solar system: Sputtering and trapping of radiation products

Abstract: Abstract. We performed quantitative laboratory radiolysis experiments on cubic water ice between 40 and 120 K, with 200 keV protons. We measured sputtering of atoms and molecules and the trapping of radiolytic molecular species. The experiments were done at fluences corresponding to exposure of the surface of the Jovian icy satellites to their radiation environment up to thousands of years. During irradiation, 02 molecules are ejected from the ice at a rate that grows roughly exponentially with temperature; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 52 publications
(38 reference statements)
4
43
0
Order By: Relevance
“…Direct excitation of matrix-isolated H 2 O 2 at low temperature also did not yield O 2 , but the production of a mobile O that reacted with (Khriachtchev et al, 2000). Irradiating with 200 keV protons at temperatures of 40-129K, Bahr et al (2001) found only about 0.001-0.02% H 2 O 2 using programmed thermal desorption as compared with earlier experiments that suggested larger values (e.g., Table 2). Using infrared absorption Moore and Hudson (2000) found a G value of ,0.1 for incident MeV protons at low temperature, but the signal in the observed band became negligible at 80K, suggesting that H 2 O 2 was not being formed.…”
Section: Precursor State and Peroxidementioning
confidence: 64%
“…Direct excitation of matrix-isolated H 2 O 2 at low temperature also did not yield O 2 , but the production of a mobile O that reacted with (Khriachtchev et al, 2000). Irradiating with 200 keV protons at temperatures of 40-129K, Bahr et al (2001) found only about 0.001-0.02% H 2 O 2 using programmed thermal desorption as compared with earlier experiments that suggested larger values (e.g., Table 2). Using infrared absorption Moore and Hudson (2000) found a G value of ,0.1 for incident MeV protons at low temperature, but the signal in the observed band became negligible at 80K, suggesting that H 2 O 2 was not being formed.…”
Section: Precursor State and Peroxidementioning
confidence: 64%
“…The onset of this current indicates the vacuum level energy within an uncertainty of ±0.3 eV (Sanche, 1979). After electron bombardment, the D 2 O 2 and DO 2 yields were measured with the QMS by evaporating the film by resistive heating of the Pt foil (Bahr et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…They found that the produced H 2 O 2 /H 2 O ratio is greater for the heavier ions ($6% for the case of Ar ++ ; only $1% for H + ). Bahr et al (2001) conducted quantitative laboratory radiolysis experiments on cubic water ice between 40 and 120 K with 200 keV protons. They found that trapped O 2 and H 2 O 2 can be released from the irradiated ice upon warming.…”
Section: Introductionmentioning
confidence: 99%